The influence of nanoclay on the performance properties and moisture susceptibility of rubberized asphalt mixture. (17th January 2017) - Amini, A.; Goli, A.; Ziari, H.
ABSTRACT: The authors investigated the effect of nanoclay (NC) on the performance properties and moisture susceptibility of rubberized asphalt mixtures. Two percent crumb rubber modifier (CRM) and NC in both combined and separate modes and the effects of each additive on bitumen performance were examined through administering tests of penetration grade, softening point and temperature susceptibility. Also, indirect tensile strength tests in both dry and saturated states were performed to allow for measuring the moisture susceptibility of asphalt mixtures. Moreover, the effect size of both additives on improving the bitumen performance and asphalt mixtures was assessed by running analysis of variance method and sensitivity analysis. The results of the laboratory test and statistical analyses revealed that CRM and NC improved the properties of bitumen and asphalt mixtures. This improvement was associated with the content and type of the additives applied, and also bitumen and asphalt mixtures had the best performance in presence of a combination of CRM and NC.